Mobile Based Application Design of the Catholic Church of the Redeemer of Sumbawa Using the Waterfall Method - Araujo, Claudio Orlando De; Zakariyah, Muhammad (JISA(Jurnal Informatika dan Sains), 2023)
The church is a gathering place for Christians to carry out worship. The Sumbawa Redeemer Catholic Church is a church that originates from Sumbawa Besar Regency, West Nusa Tenggara Province. This Catholic Church is the only church in Sumbawa Regency. The purpose of this research is to make the Application of the Catholic Church of the Redeemer of Sumbawa. using the waterfall design method and the ADDIE model. The data collection method was carried out using the Unified Modeling Language (UML) method, use cases and activity diagrams ere used as analysis and design tools. The programming languages used include Kotlin and Java, the software used includes the IDE Android Studio 4.0, MS. This research yielded results, namely a program that can be used to make it easier for people to find information about the Sumbawa Redeemer Catholic Church